PRELIMINARY REPORT ON THE BIOMASS OF MACROPLANKTON AND MICRONEKTON COLLECTED WITH A BONGO NET DURING THE UMITAKA MARU FIBEX CRUISE (Collected Abstracts of Transactions of the Tokyo University of Fisheries No. 5,March 1982) - MARUYAMA, Takashi; TOYODA, Hiroshi; SUZUKI, Shigemi (1982)
P(論文) departmental bulletin paper